Perancangan Co-Library Space di Tangerang Selatan dengan Konsep Arsitektur Ekspresionis - Ghildania Chrismutiara Dewi; Sri Kurniasih; Anggraeni Dyah Sulistiowati (MAESTRO, 2022)
The need for facilities that can support education and office activities in the city of South Tangerang is increasing. Public facilities are needed such as libraries to support public knowledge and Co-Working Space to facilitate office workers. With the construction of Co-Library Space in South Tangerang which has the necessary facilities, it is expected to increase the productivity of the community in learning and working activities. To be able to increase public interest, this Co-Library Space building uses the concept of Expressionist Architecture. The use of this concept in the design of Co-Library Space aims to describe the nature of perseverance and steadfast and provide freedom of expression and explore new things for everyone who comes to visit.